Glaucomatous-type optic discs in high myopia - Nagaoka, Natsuko; Jonas, Jost B. (PLOS ONE, 2015)
Purpose To assess the prevalence of glaucoma in patients with high myopia defined as myopic refractive error of >-8 diopters or axial length ≥26.5 mm. Methods The hospital-based observational study included 172 patients (336 eyes) with a mean age of 61.9±12.3 years and mean axial length of 30.1±2.3 mm (range: 24.7-39.1mm). Glaucomatous-type optic discs were defined by glaucomatous optic disc appearance. Glaucoma was defined by glaucomatous optic disc appearance and glaucomatous Goldmann visual field defects not corresponding with myopic macular changes. Results Larger disc area (mean: 3.18±1.94 mm2) was associated with longer axial length (P<0.001; standardized correlation coefficient: 0.45). Glaucoma was detected in 94 (28%; 95% Confidence intervals: 23%, 33%) eyes. In multivariate analysis, glaucoma prevalence was 3.2 times higher (P<0.001) in megalodiscs (>3.79 mm2) than in normal-sized discs or small discs (<1.51 mm2) after adjusting for older age. Axial length was not significantly (P = 0.38) associated with glaucoma prevalence in that model. Glaucoma prevalence increased by a factor of 1.39 for each increase in optic disc area by one mm2. Again, axial length was not significantly (P = 0.38) associated with glaucoma prevalence when added to this multivariate model. Conclusion Within highly myopic individuals, glaucoma prevalence increased with larger optic disc size beyond a disc area of 3.8 mm2. Highly myopic megalodiscs as compared to normal sized discs or small discs had a 3.2 times higher risk for glaucomatous optic nerve neuropathy. The increased glaucoma prevalence in axial high myopia was primarily associated with axial myopia associated disc enlargement and not with axial elongation itself.